2014
DOI: 10.1136/jnnp-2014-308452
|View full text |Cite
|
Sign up to set email alerts
|

Different electrophysiological profiles and treatment response in ‘typical’ and ‘atypical’ chronic inflammatory demyelinating polyneuropathy

Abstract: Among the CIDP spectrum, typical CIDP and MADSAM are the major subtypes, and their pathophysiology appears to be distinct. In typical CIDP, the distal nerve terminals and possibly the nerve roots, where the blood-nerve barrier is anatomically deficient, are preferentially affected, raising the possibility of antibody-mediated demyelination, whereas cellular immunity with breakdown of the barrier may be important in MADSAM neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
127
2
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(147 citation statements)
references
References 32 publications
10
127
2
8
Order By: Relevance
“…Distribution patterns of conduction abnormalities was demonstrated to determine clinical phenotypes 19. It was also reported that electrophysiological profiles and treatment response were different between typical CIDP and MADSAM 10. Our results corroborate and expand findings of previous reports on the clinical–electrophysiological correlations in typical and atypical CIDP.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Distribution patterns of conduction abnormalities was demonstrated to determine clinical phenotypes 19. It was also reported that electrophysiological profiles and treatment response were different between typical CIDP and MADSAM 10. Our results corroborate and expand findings of previous reports on the clinical–electrophysiological correlations in typical and atypical CIDP.…”
Section: Discussionsupporting
confidence: 90%
“…Because no formal clinical diagnostic criteria were available for these atypical subtypes, we adopted the following operational definitions as described in previous studies. MADSAM is defined as a typical mononeuropathy multiplex, and the asymmetry of weakness is determined as differences in muscle strength by one or more Medical Research Council (MRC) scales in the homonymous muscles 10. DADS is defined as a predominantly distal and symmetric sensorimotor polyneuropathy sparing proximal limb muscles 9.…”
Section: Methodsmentioning
confidence: 99%
“…A better response to IVIg than to steroids was reported in some series of patients with LSS,4 5 7 16 17 while others6 reported a reduced response to IVIg but not to steroids compared with typical CIDP. Patients with DADS were reported to have a less satisfactory response to treatment than patients with typical CIDP 18 19.…”
Section: Discussionmentioning
confidence: 91%
“…CIDP is an autoimmune-mediated peripheral nerve disease, with segmental demyelination and remyelination resulting in onion bulb formation and varying degrees of interstitial edema and endoneurial inflammation (7). The clinical presentation of CIDP is variable, including typical (proximal and distal weakness with large-fiber sensory loss), atypical (distal large-fiber sensorimotor neuropathy), and multifocal sensorimotor neuropathy (Lewis–Sumner syndrome) (8, 9). The heterogeneous morphology by ultrasound may reflect both the clinical and pathological heterogeneities of the disease.…”
Section: Discussionmentioning
confidence: 99%